Gizzard Shad Target Strength‐to‐Body Size Equations at Multiple Hydroacoustic Frequencies. Issue 2 (12th March 2021) - Johnson, Garret R.; Dillon, Rebecca A.; Zweifel, Richard D.; Ludsin, Stuart A.; Conroy, Joseph D.
Abstract: Species‐specific target strength (TS)‐to‐length ( L ) and TS‐to‐weight ( W ) equations can reduce bias in biomass estimates from hydroacoustic surveys, yet these equations do not exist for most fishes. Equations specific to the Gizzard Shad Dorosoma cepedianum, a wide‐ranging and often highly abundant prey fish in North American reservoirs and rivers, do not exist. Herein, we sought to develop TS– L and TS– W equations for Gizzard Shad by insonifying free‐swimming individuals of known sizes (36–209 mm TL) in a net cage at three transducer frequencies (70, 120, and 200 kHz). We derived TS–size relationships using major‐axis regression (MAR) and least‐squares regression (LSR), comparing our resultant TS– L equations to a commonly used multispecies equation (Love 1971). To determine how our Gizzard Shad‐specific equations affected estimates of prey fish biomass, we conducted mobile hydroacoustic surveys in four small, shallow Midwestern reservoirs and then estimated biomass using each equation. In general, for TS– L equations, MAR produced the highest estimates of biomass, followed by LSR and then the multispecies equation. Similarly, the TS– W equation derived using MAR produced greater biomass estimates than the equation using LSR. Our findings highlight the value of using species‐specific TS–size equations over multispecies equations in ecosystems dominated by a single fish species (e.g., Gizzard Shad in Midwestern reservoirs). They also demonstrate the value of using MAR to develop TS–size equations, owing to its ability to account for fish size measurement error. The use of species‐specific TS–size equations and MAR should lead to robust estimates of biomass in single‐species‐dominated ecosystems, thus benefiting fisheries assessment and decision making.